Some factors affecting innovation activities of enterprises in Nghe An Province, Vietnam - Phan, Thao Huong; Dao, Ha Ngoc; Ha, Ngoc Huy; Trang, Tran Mai (International Journal of Innovative Research and Scientific Studies, 2025)
Innovation plays an important role in the operation of enterprises. It helps enterprises develop competitiveness, improve products and services, enhance product quality, and increase profits. This study employs quantitative methods to evaluate the factors affecting the innovation activities of enterprises in Vinh City, Nghe An Province, Vietnam. The study surveyed 150 enterprises operating in Vinh City, Nghe An Province. The OLS regression model was used to assess the impact of each factor on the innovation activities of enterprises. The research results indicate that the key factors positively influencing the innovation activities of enterprises in Vinh City, Nghe An Province, include legal factors, human resources, regional connectivity, support services, technological factors, and infrastructure. Based on the research findings, the authors provide several recommendations for businesses in Vinh City to further enhance their innovation activities, thereby promoting the economic development of Nghe An Province.